2017
DOI: 10.1186/s12954-017-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

Opiate agonist treatment to improve health of individuals with opioid use disorder in Lebanon

Abstract: BackgroundOpioid agonist therapy has been widely used to reduce harms among individuals with opioid use disorder but its effectiveness has not been evaluated in the Middle East North African (MENA) region. This study aims to evaluate the effectiveness of a program using opioid agonist therapy in combination with psychosocial support on improving psychological and social well-being, reducing arrest, and reducing risky behavior in individuals with opioid use disorder in Lebanon.MethodsA one-group pre-test post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…A longitudinal study by the same researchers and a different cohort examined the effects of OAT and psychosocial support on opioid-dependent males at the first outpatient community-based treatment centre in Lebanon. 48 An observational case series of 24 opiate-dependent participants evaluated the effects of a double naltrexone implant treatment. Patients travelled from Mauritius to Australia to undergo surgery and follow-ups were done in Mauritius.…”
Section: Combined Pharmacological-psycho-social-educational Intervent...mentioning
confidence: 99%
See 2 more Smart Citations
“…A longitudinal study by the same researchers and a different cohort examined the effects of OAT and psychosocial support on opioid-dependent males at the first outpatient community-based treatment centre in Lebanon. 48 An observational case series of 24 opiate-dependent participants evaluated the effects of a double naltrexone implant treatment. Patients travelled from Mauritius to Australia to undergo surgery and follow-ups were done in Mauritius.…”
Section: Combined Pharmacological-psycho-social-educational Intervent...mentioning
confidence: 99%
“…Vo et al 40 Young adult alternative treatment program (YAAP) Sigmon et al 42 Buprenorphine-naloxone stabilization and naltrexone therapy with behaviour therapy Vo et al 41 Home-based delivery of extended-release naltrexone Ruisenōr-Escudero et al 45 Opioid substitution therapy clinic Romero-Gonzalez et al 46 Buprenorphine-naloxone medication with group cognitive behavioural therapy Ghaddar et al 47 Opioid agonist therapy program Ghaddar et al 48 Opiate agonist treatment Gonzalez et al 43 Buprenorphine-Naloxone therapy with or without memantine Jhugroo et al 49 Sustained-release naltrexone implant Law et al 44 Detoxification and opioid substitution therapy Schuman-Olivier et al 50 Collaborative care buprenorphine treatment program The MATA study indicated that missing urine drug screening rates were low and buprenorphine-naloxone compliance rates and opioid abstinence rates were high while youth were engaged with the clinic. Retention was a major barrier to the success of treatment; 75% returned for a second visit, after one visit, at 2 months, 45% of patients were retained and at 1 year, 9% of patients were active in the program.…”
Section: Combined Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of population health, outcomes could be overdose mortality rate (12), prevalence of HIV (13) and hepatitis C virus infection acquisition (14), or cessation of injection drug use (15). From the perspective of the individuals health, controlled trials often assess the outcome as the time to opioid relapse (16), retention in treatment (17), self-reported craving and opioid withdrawal symptoms (18), opioid-positive urine drug tests (10), psychological and social well-being (19), or quality of life (20). However, there is no consensus as to which could be the most appropriate outcome measure.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative evaluation of the OAT program in Lebanon has recently been conducted [ 23 ]. Although the program produced positive outcomes on quality of life, mental and social wellbeing and reduction of risky behavior among users, very low retention rates has been observed.…”
Section: Introductionmentioning
confidence: 99%